Habermas and the "reflexive" structure of law - Melo, Rúrion Soares (2005)
HABERMAS INTENDED TO EXPLAIN THAT THE CONCEPTION OF A LOGICAL GENESIS OF RIGHTS IS EXPLICITLY DESCRIBED AS A CIRCULAR PROCESS IN WICH THE LIBERTIES OF AUTONOMOUS PRIVATE INDIVIDUALS AND THE RIGHTS OF POLITICALLY AUTONOMOS CITIZENS TO PARTICIPATE IN THE DEMOCRATIC LAW-MAKING PROCESS ARE CONSTITUTED “EQUIPRIMORDIALLY”. ACORDING TO THIS IDEA, IT CORRESPONDS TO THE “REFLEXIVE” STRUCTURE OF THE LAW, ONCE THE FORM OF LAW ORGANIZES THE DEMOCRATIC PROCESS ITSELF AND THEREFORE MUST ENGENDER THE CONDITIONS TO ITS OWN LEGITIMACY. AGAINST A LIBERAL ACCOUNT OF HABERMAS’S RECONSTRUCTION OF THE SISTEM OF RIGTHS, WE WILL SKETCH WHAT WE THINK TO BE A “CORRECT” UNDERSTANDING OF THIS “REFLEXIVE” STRUCTURE